Complications of herpes zoster in cancer patients. (July 2014) - Tran, Trung N.; Ray, G. Thomas; Horberg, Michael A.; Yawn, Barbara P.; Castillo, Adrienne L.; Saddier, Patricia; Habel, Laurel A.
Abstract Cancer patients tend to have a higher incidence of herpes zoster (HZ), but little is known about their risk of HZ complications. We conducted a retrospective study of 424 newly diagnosed hematologic (HM, n = 140) and solid tumor malignancy (STM, n = 284) patients who developed HZ between January 2001 and December 2006 to measure the frequency and identify risk factors of HZ complications. Patients were adult members of Kaiser Permanente Northern California. HZ diagnosis and complications were confirmed by medical chart review. HM patients with HZ tended to have more HZ complications than STM patients (34% vs 23%, p = 0.02), largely due to more frequent non-pain complications. On multivariate analysis, older age and being male were associated with a higher risk of HZ complications in HM patients; more advanced cancer stage was associated with HZ complications in STM patients. HZ complications are frequent and can present extra disease burden in cancer patients who develop HZ.